Grazing history effects on above-and below-ground litter decomposition and nutrient cycling in two co-occurring grasses - Semmartin, María (2007)
Fil: Semmartin, María. Universidad de Buenos Aires (UBA). Facultad de Agronomía. Instituto de Investigaciones Fisiológicas y Ecológicas vinculadas a la Agricultura (IFEVA); Argentina.